Parable of the talents - Butler, Octavia E. (New York : Aspect, 2001)
A Christian fundamentalist group kidnaps children to raise them in Christian homes in this tale of religious intolerance in a future America. The story is told by a woman at the receiving end of their zeal, the founder of a religion which they consider heathen. By the author of Parable of the Sower.
Sequel to: Parable of the sower.
Winner of the Nebula Award for Best Novel, 1952.
Keywords: Young women -- Fiction; Twenty-first century -- Fiction; Political fiction; Science fiction